Opinion of nurses of surgical departments on musculoskeletal pain - Kinga Kulczycka; Mateusz Czajka; Ewa Stychno; Bogumiła Kosicka; Mariola Janiszewska (Kazimierz Wielki University, 2018)
Introduction Musculoskeletal pains have been around for a long time but in recent years the frequency of their occurrence has increased significantly. It is a problem that occurs in an increasingly larger and younger part of society. The aim of the study was to find out the opinions of nurses of surgical departments on the occurrence of musculoskeletal pains. Data and process The research was conducted in a group of 100 people in surgical departments, in 4 hospitals in Lublin in 2016. The study involved both the author's questionnaire, which included questions allowing to determine the specificity of the work, and the Nordic questionnaire, which allowed to determine the place and frequency of pain, and the scale of Vas. Findings Nurses working in surgical departments are a group exposed to musculoskeletal pain. The specificity of work related to the necessity to perform specific tasks: care, transport, instrumental, and external load are most often the cause of pain. Demographic variables have a significant impact on the ailments experienced Conclusions Age, work experience , number of worksites and BMI are the variables that determine pain incidence in 91% of respondents. The most common pain conditions are chronic and the average pain is determined at the level of 4. 64 on a 10-point scale.